Brief Affect Recognition Thresholds: A Systematic Evaluation of The Japanese and Caucasian Brief Affect Recognition Test - Chamberland, Justin (Université d'Ottawa / University of Ottawa, 2023)
Micro-expressions are brief facial expressions of emotion (40 to 500 ms) that are posited to represent true reflections of an individual’s emotional state that have 'leaked’ through voluntary attempts to neutralize or mask the involuntary expression. As such, correct recognition can have important benefits. The Japanese and Caucasian Brief Affect Recognition Task (JACBART) has been proposed as the standardized measure of affect recognition capabilities with micro-expression durations (i.e., facial expressions lasting less than 500 ms). In this paradigm target expressions of emotion are briefly presented between two neutral expressions. However, limited research has explored the temporal thresholds and the various factors that may influence performance in a JACBART paradigm. In three studies, the current thesis sought to determine the effects of a forward mask with a variable duration (Study 1), the inclusion/exclusion of a ‘neutral’ response category (Study 2), and expressions portrayed at lower intensities (Study 3). Although a variable-duration forward mask was found to have little effect on performance, significant effects were observed for the inclusion of a ‘neutral’ response option and when reducing the expression intensity. In addition, a trend was observed across all three studies that demonstrated a recognition advantage for expressions of happiness and surprise. Performances for these two expressions exceeded the psychometric threshold with durations of as little as 5 to 10 ms, whereas presentation times as long as 113 ms were necessary to elicit above-threshold recognition rates with negative emotions (i.e., anger, disgust, fear, and sadness). Altogether, the current findings present some methodological considerations for studies interested in measuring brief affect recognition with a JACBART paradigm. More generally, they expand our understanding of how various relevant factors affect the speed at which facial expressions can be processed.
Keywords: Emotion; Brief Expression; Micro-Expression; Recognition